PENGARUH PEMBERIAN BERBAGAI KONSENTRASI BIOINOKULUM PLUS TERHADAP HASIL TANAMAN BAWANG MERAH KULTIVAR ROTE - Eko Hary Agustin Juwaningsih; Ricardo Sastra R. Longa; I Komang Sudarma (Politeknik Pertanian Negeri Kupang, 2022)
This study aims to determine the effect of various concentrations of POC Bio-Inoculum Plus on the yield of “Rote” Shallots. The design used was a Randomized Block Design (RAK). The treatment tested was the concentration of POC Bio-Inoculum which consisted of 6 levels which were: without POC 0 ml/l water, 2.5 ml/l, 5 ml/l, 7.5 ml/l, 10 ml/l and 12.5 ml/l. Based on the observations that (1) The concentration of POC Bio-Inoculum Plus affected the number of tillers, number of tubers, plant wet weight, dry weight of shallots, (2) Treatment of POC Bio-Inoculum Plus concentration of 7.5 ml/l gave the best effect on the number of tubers per clump (8.55 bulbs), fresh weight of bulbs per clump (40.25 g), fresh weight of bulbs per plot (1.168 g), dry weight of bulbs per clump (38.45 g), and dry tubers per plot (903.25 g).Keywords: Shallots, Rote Cultivars, Concentration, POC Bio-Inoculum Plus